Nitrogen Mustards as Anticancer Chemotherapies: Historic Perspective, Current Developments and Future Trends - Diethelm-Varela, Benjamin; Ai, Yong; Liang, Dongdong; Xue, Fengtian (Current Topics in Medicinal Chemistry, 2019)
Nitrogen mustards, a family of DNA alkylating agents, marked the start of cancer pharmacotherapy. While traditionally characterized by their dose-limiting toxic effects, nitrogen mustards have been the subject of intense research efforts, which have led to safer and more effective agents. Even though the alkylating prodrug mustards were first developed decades ago, active research on ways to improve their selectivity and cytotoxic efficacy is a currently active topic of research. This review addresses the historical development of the nitrogen mustards, outlining their mechanism of action, and discussing the improvements on their therapeutic profile made through rational structure modifications. A special emphasis is made on discussing the nitrogen mustard prodrug category, with Cyclophosphamide (CPA) serving as the main highlight. Selected insights on the latest developments on nitrogen mustards are then provided, limiting such information to agents that preserve the original nitrogen mustard mechanism as their primary mode of action. Additionally, future trends that might follow in the quest to optimize these invaluable chemotherapeutic medications are succinctly suggested.
Keywords: Pharmacotherapy